Efficacy of Photobiomodulation and Vitamin D on Odontogenic Activity of Human Dental Pulp Stem Cells: Efficacy of Photobiomodulation and Vitamin D on Odontogenic Activity of HDPSCs - abdelgawad, latifa M; Salah, Nihal; Sabry, Dina A; Abdelgwad, Marwa M (Journal of Lasers in Medical Sciences, 2021)
Introduction: The regeneration of dental pulp tissue using human dental pulp stem cells (HDPSCs) has attracted increasing attention in recent years. Recent studies have suggested that several factors such as photobiomodulation (PBM) and vitamin D affect the proliferation and differentiation of HDPSCs. Therefore, the present study evaluated the effects of PBM and vitamin D on odontogenic differentiation of HDPSCs for dentin-like tissue formation. Methods: HDPSCs were collected, isolated, and characterized and then divided into six groups: group I, control; group II, vitamin D (10-7 Mol); group III, irradiation at 1 J/cm2 of 810 nm diode laser; group IV, irradiation at 1 J/cm2 and culture with vitamin D; group V, irradiation at 2 J/cm2, and group VI, irradiation at 2 J/cm2 and culture with vitamin D, cell viability assay was measured through MTT. Alkaline phosphatase (ALP) enzyme activity and mRNA levels of vascular endothelial growth factor (VEGF), bone morphogenic protein-2 (BMP-2), and dentin sialophosphoprotein (DSPP) were also assessed. Results: PBM at 1 and 2 J/cm2 combined with vitamin D significantly promoted HDPSCs proliferation through MTT assay and odontogenic differentiation through gene expression of VEGF, BMP-2, and DSPP levels (P<0.0001). Conclusion: PBM at 2 J/cm2 combined with vitamin D enhanced the HDPSCs proliferation and odontogenic differentiation and thus could be a novel strategy for dentin regeneration in dentistry. DOI: 10.34172/jlms.2021.30